An Analysis of Online Class of Postgraduate Course Conducted by Saraswati Multiple Campus during COVID-19 in Lockdown Period - Upadhyaya, Yadav Mani (Interdisciplinary Journal of Management and Social Sciences, 2021)
COVID-19 has changed the way people around the world change their daily lives. Such a change took place not only in developed countries but also in developing countries. Such daily changes took place in the educational sector of the country as well as in other sectors. As a result, Saraswati Multiple Campus also changed its old academic calendar to conduct online classes. This article aims to inform all about the online classes conducted by Saraswati Multiple Campus during the lockdown period of COVID-19. This article is descriptive. However, in general, 60 students have been asked three questions each online and the data has been collected and explained based on that. Similarly, the general method for interpreting online classes is based on online information published by Tribhuvan University at different times, online information published by the campus administration, and various online related articles. Also, the summary of this article says that the online class conducted by the campus has been effective despite various problems.